The establishment of blue-sky index: how to quantify the aerosol optical impacts on sky color - Sunan Shen; Jiandong Wang; Chao Liu; Jia Xing; Jiaping Wang; Jing Cai; Zeyuan Tian; Peng Wang; Guangjie Zheng; Yuzhi Jin; Chenggang Wang; Le Cao; et al. (Environmental Research Letters)
Color of the sky serves as a direct indicator of haze, while also exerting substantial influence on human physiological and psychological well-being, as well as the overall environmental scenery. However, quantifying color changes is quite challenging. This research develops a quantitative approach for evaluating the influence of atmospheric aerosol pollution on the appearance of the sky. We first calculated the influence of atmospheric aerosols on the sky’s diffuse radiation, which is the source of sky color. Then, we mapped the diffuse radiation onto a perceptually uniform color space to quantify alterations in sky color. The results reveal that the relationship between aerosol concentration and sky color change follows a logarithmic-like distribution: the higher the concentration, the weaker the change in sky color per unit increase in aerosol concentration. Consequently, during the early phases of air pollution control implementation, there may be minimal observable changes in the color of the sky. However, as these measures are further enforced, a discernible bluing effect on the sky will become evident. Based on the quantification of the change of sky color, a blue-sky index (BSI) was established. We find that concurrent with improvements in air quality resulting from emission reduction measures, the BSI has significantly decreased in recent years in China. This trend indicates an increase in the frequency of blue-sky occurrences.